Soil resource inventory for assessing soil quality and land capability using geospatial technology - GAHLOD, N. S.; KUMAR, Y. SURESH; CHAND, MAHESH; ARYA, V. S. (Journal of Soil and Water Conservation, 2020)
Soil survey provides information about the inherent and dynamic qualities of the soil. Soil quality assessments are thus used to evaluate the effects of management on the health of the soil. The study is based on the generation of soil and land resource database of Warangal district on 1:50,000 scale using Resourcesat-1, LISS-III satellite data and Digital Elevation Model (DEM) in Geographical Information System (GIS). It was found that the study area comprised of four major physiographic regions viz. pediplain (80.9 %), undifferentiated hill slopes (8.0 %), pediments (6.3 %), alluvial plains (4.8 %) and soils were classified under Entisols, Inceptisols, Alfisols and Vertisols orders. The land capability assessment of identified mapping units showed that around 44.4% of the Total Geographical Area (TGA) which mainly falls in agriculture was classified under land capability class II and II-III and has the soil quality issues with respect to soil pH, Electrical Conductivity (E.C.) and texture. About 8.1 % area found under class III in agriculture and plantation having potential limitations of unfavourable soil texture, moderate salinity, whereas, 5.4 % area under open scrub was classified under class III-IV and suffers from root zone limitation, low organic carbon, unfavourable texture, susceptibility for erosion. About 8.7 % area fall under open scrub/ waste land placed under class IV and VI due to adverse effect of past erosion on soil quality imposed mainly due to faulty land use and unfavourable landform. It was observed that 27.5 % area was covered under notified/ restricted forest and 5.9 % area under miscellaneous uses like settlements or water bodies etc. These areas were not studied for their land capabilities. The spatial database created in GIS will be of immense use for the academicians and planners to identify problematic areas and to suggest sustainable action plan for development of agriculture, horticulture, forestry, etc.